Review of the economic evidence presented to the United States Advisory Committee on Immunization Practices, 2012–2016. Issue 1 (3rd January 2019) - Pike, Jamison; Leidner, Andrew J.; MacNeil, Jessica R.; Cohn, Amanda C.
Highlights: Overall, studies were transparent, e.g. inclusion of a clearly stated study perspective. For consistency, we examined the frequency of particular model characteristics. We find opportunity for improvement in costs included and sensitivity analyses. We find these presentations contribute beneficially to the ACIP policy-making process. Abstract: We identified 16 Advisory Committee on Immunization Practices (ACIP) presentations from 2012 to 2016 that indicated 'cost' or 'economic' content. Characteristics were reviewed, abstracted, and tabulated to quantify and assess the transparency and consistency of economic evidence presented to ACIP. To assess transparency, we documented if each study identified author affiliation, conflicts of interest, study limitations, a clearly described model structure and other model attributes. To assess consistency, we identified the frequency of specific modeling choices, including the perspective, types of health outcomes considered, inclusion of specific types of costs, discount rate, and use of sensitivity analyses. Our results indicate that the content in these presentations appear to be transparent overall and consistent in several important areas, such as study perspective and health outcomes. However, we find the inclusion of particular types of direct costs, indirect costs, program costs, and sensitivity analyses are areas that could improve consistency.